INSTAGRAM AS AN INNOVATIVE MEDIUM FOR ENHANCING ENGLISH PRONUNCIATION SKILLS: AN ANALYSIS OF COLLEGE STUDENT PERCEPTIONS (INTERNATIONAL SEMINAR, 2024)
This study investigates the perceptions of college students regarding Instagram as an innovative medium for enhancing English pronunciation skills. With the rise of social media as a tool for language learning, this research aims to explore how students utilize Instagram to improve their pronunciation abilities and the effectiveness of this platform in achieving their language learning goals. Utilizing a qualitative descriptive approach, data will be collected through surveys administered to students who actively engage with English language content on Instagram. The survey will include open-ended questions designed to capture students' experiences, motivations, and challenges encountered while using Instagram for pronunciation practice. By analyzing the responses, the study seeks to identify common themes and insights regarding the impact of Instagram on students' pronunciation skills, as well as their overall perceptions of its usefulness as a learning tool. The findings are expected to contribute valuable information to educators and content creators about effective practices in leveraging social media for language education, particularly in enhancing pronunciation skills among learners. Ultimately, this research highlights the potential of Instagram not only as a social networking site but also as a dynamic resource for language acquisition in the digital age.